Copper-based static disc material for aviation and preparation method of copper-based static disc material

By adopting a variety of ingredients and advanced processes such as high -pure electrolytic copper, the air -based copper -based static disk materials with excellent comprehensive performance have been prepared to solve the problem of lack of performance in existing materials in the aerospace brake system. High -efficiency braking and long life under high temperature environment.

CN119372568APending Publication Date: 2025-01-28YOUCAITEC MATERIAL CO LTD

Patent Information

Application Number
CN202411962425.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The comprehensive performance of existing copper-based static disc materials is weak and cannot meet the high requirements of aerospace brake systems, especially in high-speed braking and high-temperature environments.

Method used

Adopt high -pure electrolytic copper, aluminum bronze alloy, nani nickel powder, chromium molybdenum alloy, nano -silicon carbide particles, continuous carbon fiber bundles, six -way boron nanomoltic tablets, tungsten carbide particles, multi -layer graphene, sodium molybdenum acid, coupling agent, coupling agent , Nano -lubricant and antioxidants, through vacuum sensing, ball mill, heat and other processes such as static pressure, sintering and heat squeezing, prepare a copper -based static disk material with excellent comprehensive performance.

Benefits of technology

It significantly improves the strength, hardness, high temperature wear resistance, friction coefficient stability and corrosion resistance of the material, and can maintain the structural stability and efficient braking performance in a complex aerospace environment, and extend the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372568A_ABST
    Figure CN119372568A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of aviation static disc materials, and aims to solve the problem that the application of an existing copper-based static disc material in an aviation brake system is limited due to the fact that the comprehensive performance of the existing copper-based static disc material is weak. In order to achieve the purpose, the invention provides the aviation copper-based static disc material and the preparation method thereof. The aviation copper-based static disc material comprises, by mass, 55%-65% of high-purity electrolytic copper, 10%-15% of aluminum bronze alloy, 4%-8% of nano nickel powder, 2%-5% of chromium molybdenum alloy, 2%-6% of nano silicon carbide particles, 1.5%-4% of continuous carbon fiber bundles, 1%-3% of hexagonal boron nitride nanosheets, 0.5%-2% of tungsten carbide particles, 0.5%-2% of multilayer graphene, 0.3%-1.5% of sodium molybdate, 0.5%-1.5% of a coupling agent, 0.2%-1% of a nano lubricant and 0.1%-0.8% of an antioxidant. The comprehensive properties such as strength, hardness, high-temperature wear resistance, friction coefficient stability and corrosion resistance of the aviation copper-based static disc material are remarkably improved, the requirements of an aviation brake system are met, and the aviation copper-based static disc material is particularly suitable for being applied under complex working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aircraft static disk materials, and in particular to an aircraft copper-based static disk material and a preparation method thereof. Background Art

[0002] In the aerospace field, the braking system is one of the key subsystems to ensure the safe take-off, landing and operation of aircraft. The performance of the stator, as the core component of the braking system, is directly related to the safety and reliability of the entire flight mission. With the continuous advancement of aerospace technology, the speed of aircraft continues to increase, the load continues to increase, and the requirements for braking performance are becoming more and more stringent, which poses extremely severe challenges to the material of the stator.

[0003] Traditional stator disc materials have gradually shown many limitations when responding to the braking needs of modern aerospace vehicles. For example, some commonly used metal stator disc materials, such as steel, have certain strength and wear resistance, but have a high density, which not only increases the overall weight of the aircraft, but is not conducive to the improvement of fuel economy and payload. In addition, during high-speed braking, its heat dissipation performance is relatively poor, and it is easy for heat accumulation to cause the stator disc temperature to rise sharply, thereby causing the risk of brake failure. In addition, the friction coefficient of traditional stator disc materials is not stable enough. After multiple braking cycles, the friction coefficient will change significantly, making it difficult to accurately control the braking effect, posing a potential threat to flight safety.

[0004] Specifically, when an aerospace vehicle brakes, the microscopic environment of the stator is extremely complex and harsh. During high-speed friction, the microstructure of the stator surface will change dramatically. Local high temperature can cause atoms on the surface of the material to diffuse, migrate or even melt, resulting in uneven tissue structure on the surface of the material, affecting its tribological and mechanical properties. At the same time, the huge pressure generated during the braking process will cause the microscopic defects (such as pores, dislocations, etc.) inside the material to expand and interact with each other, accelerating fatigue damage and wear of the material. Moreover, the special operating environment of aerospace vehicles, such as low temperature and low pressure at high altitudes and possible exposure to various chemical pollutants on airport runways, will make the stator material more susceptible to erosion and damage at the microscopic level. For example, some corrosive substances may penetrate into the microstructure of the material, react chemically with the constituent elements of the material, and weaken the strength and stability of the material.

[0005] In the prior art, copper-based materials have become one of the potential candidate materials because of their relatively high thermal conductivity and good processing performance. However, pure copper or ordinary copper alloys still cannot meet the strict requirements of aerospace stator discs in terms of strength, hardness and high-temperature wear resistance. For example, their lower hardness makes it easy to cause excessive wear during high-speed and high-load braking, and the rapid decay of their mechanical properties under high-temperature environments can cause deformation and failure of the stator disc. Therefore, how to optimize the composition design of copper-based materials, thereby maintaining the inherent advantages of copper-based materials while significantly improving their comprehensive performance such as strength, hardness, high-temperature wear resistance, friction coefficient stability and corrosion resistance, has become a key technical problem that urgently needs to be overcome in the research field of aerospace stator disc materials.

[0006] In view of this, the art needs an aviation copper-based static disk material and a preparation method thereof to solve the above problems. Summary of the invention

[0007] In order to solve the above technical problems, that is, to solve the problem that the existing copper-based static disk materials have weak comprehensive performance and thus are limited in application in aviation brake systems.

[0008] In one aspect, the present invention provides an aviation copper-based static disk material, which comprises, by mass percentage, 55%-65% high-purity electrolytic copper, 10%-15% aluminum bronze alloy, 4%-8% nano-nickel powder, 2%-5% chromium-molybdenum alloy, 2%-6% nano-silicon carbide particles, 1.5%-4% continuous carbon fiber bundles, 1%-3% hexagonal boron nitride nanosheets, 0.5%-2% tungsten carbide particles, 0.5%-2% multilayer graphene, 0.3%-1.5% sodium molybdate, 0.5-1.5% coupling agent, 0.2%-1% nano-lubricant and 0.1%-0.8% antioxidant.

[0009] In certain preferred embodiments, the coupling agent includes 0.3%-0.9% of a silane coupling agent and 0.2%-0.6% of a titanate coupling agent.

[0010] In certain preferred embodiments, the nano-lubricant includes 0.1%-0.5% nano-molybdenum disulfide and 0.1%-0.5% nano-zinc borate.

[0011] In certain preferred embodiments, the antioxidant comprises 0.05%-0.4% of a hindered phenol antioxidant and 0.05%-0.4% of a phosphite antioxidant.

[0012] The aviation copper-based static disk material of the present invention has the following beneficial effects: The aviation copper-based static disc material of the present invention has excellent comprehensive properties. Specifically, ultra-high purity electrolytic copper imparts good electrical conductivity, thermal conductivity and ductility, aluminum bronze alloy is specially treated to improve strength, hardness, wear resistance and corrosion resistance, nano nickel powder enhances strength and corrosion resistance, chromium molybdenum alloy improves high temperature strength and oxidation resistance, and together constructs excellent comprehensive mechanical properties, so that it can effectively resist wear, deformation and high temperature damage under the harsh stress and environmental conditions of aerospace brake disc braking, and ensure structural integrity and service life. Nano silicon carbide particles, continuous carbon fiber bundles, hexagonal boron nitride nanosheets, and tungsten carbide particles respectively improve the material's hardness, wear resistance, tribological properties and structural stability with their unique properties, multilayer graphene and sodium molybdate synergistically play a lubricating and anti-wear role, ensuring stable and reliable tribological properties under different working conditions, maintaining the consistency of braking effect, multifunctional coupling agents enhance component bonding and material stability, nano lubricants assist processing and assist performance during use, and antioxidant complexes delay oxidative aging, and together ensure the material's good processing performance and long-term stability and reliability, meeting the high standards for brake disc materials in the aerospace field.

[0013] In another aspect, the present invention further provides a method for preparing the above-mentioned aviation copper-based static disk material, the preparation method comprising: S1: Pretreatment of high-purity electrolytic copper, aluminum bronze alloy, nano nickel powder, chromium-molybdenum alloy, nano silicon carbide particles, continuous carbon fiber bundles, hexagonal boron nitride nanosheets and tungsten carbide particles; S2: adding the pretreated high-purity electrolytic copper, aluminum bronze alloy, nano nickel powder, chromium-molybdenum alloy, nano silicon carbide particles, continuous carbon fiber bundles, hexagonal boron nitride nanosheets and tungsten carbide particles, multilayer graphene, sodium molybdate, coupling agent, nano lubricant and antioxidant into a high energy ball mill for ball milling; S3: loading the mixed powder into a mold, and then placing the mold in a hot isostatic pressing device for hot isostatic pressing; S4: placing the formed green body into a vacuum sintering furnace and sintering it in a staged heating manner, and then performing hot extrusion treatment; S5: Mechanically process and surface treat the sintered copper-based static disk material.

[0014] In some preferred embodiments, step S1 specifically includes: S11: placing high-purity electrolytic copper, aluminum bronze alloy, nano nickel powder and chromium-molybdenum alloy in a vacuum induction melting furnace for vacuum induction melting, the melting temperature is 1300-1500° C., the melting time is 3-5 hours, during the vacuum induction melting process, the metal alloy is treated by a combination of electromagnetic stirring and ultrasonic treatment, and then the melted alloy is cooled, hot rolled, annealed and crushed in sequence; S12: soaking the nano-silicon carbide particles in a dopamine solution, wherein the concentration of the dopamine solution is 2-4 g / L and the pH value is 8-9, stirring and reacting at room temperature for 24-48 hours, then taking out the nano-silicon carbide particles and rinsing them with deionized water, and drying them at 80-100° C. for 4-6 hours; S13: treating the continuous carbon fiber bundle with plasma for 1-2 hours at a power of 500-1000 W, then impregnating the continuous carbon fiber bundle with a silane coupling agent for 2-4 hours at a temperature of 60-80° C., and drying the treated continuous carbon fiber bundle at 100-120° C. for 3-5 hours; S14: soaking the hexagonal boron nitride nanosheets in a sodium hydroxide solution with a concentration of 1-2 mol / L, stirring the solution at 80-100° C. for 2-4 hours, then washing with deionized water until neutral, drying at 100-120° C. for 4-6 hours, and then modifying the nanosheets with a silane coupling agent for 2-4 hours at a temperature of 60-80° C.; S15: ball milling the tungsten carbide particles, using zirconium oxide balls as the ball milling medium, a ball-to-material ratio of (8-12):1, and a ball milling time of 15-20 hours. The ball milled tungsten carbide particles are dried at 80-100° C. for 4-6 hours.

[0015] In certain preferred embodiments, in step S2, the rotation speed of the high energy ball mill is 300-500 r / min, the ball milling time is 6-10 hours, during the ball milling process, a dispersant is added, and then the ball milled powder is vacuum dried at a drying temperature of 80-100°C for 4-6 hours.

[0016] In certain preferred embodiments, in step S3, the temperature of hot isostatic pressing is 800-1000°C, the pressure is 150-200 MPa, and the holding time is 2-4 hours.

[0017] In some preferred embodiments, in step S4, the vacuum sintering furnace is first heated to 600-800°C at a rate of 5-10°C / min, kept at this temperature for 1-2 hours, and then heated to a sintering temperature of 1000-1200°C at a rate of 3-5°C / min, kept at this temperature for 3-4 hours. The vacuum degree of the vacuum sintering furnace is 1×10 -4 -1×10 -3 Pa, the temperature of hot extrusion treatment is 750-900℃, and the extrusion ratio is (15-25):1.

[0018] In some preferred embodiments, in step S5, the surface treatment method is: the surface is subjected to aluminum oxide sandblasting at a pressure of 0.3-0.6 MPa, the treatment particle size is 20-40 mesh, and then a wear-resistant coating is sprayed with a thickness of 0.05-0.2 mm, and then nitrogen ion implantation is performed, the energy of the injected nitrogen ions is 50-100 keV, and the dosage is .

[0019] The preparation method of the aviation copper-based static disk material of the present invention has the following beneficial effects: In the preparation method of the aviation copper-based stator material of the present invention, during the raw material pretreatment stage, vacuum induction melting and subsequent treatment of various metal components ensure the uniformity of components, refine grains and optimize the organizational structure, thereby improving the material strength and processing performance; targeted surface treatment of the strengthening phase effectively improves its bonding and compatibility with the copper-based alloy, promotes its uniform dispersion to give full play to the reinforcing effect; the powder mixing step achieves full and uniform mixing of various components through high-energy ball milling and dispersant addition with specific parameters, laying the foundation for the preparation of high-quality materials; the hot isostatic pressing process densifies the powder, eliminates defects and significantly improves the material density and mechanical properties to meet the high strength and high reliability requirements of the brake disc; the sintering process further densifies the material and stabilizes the organizational structure under a suitable vacuum environment and reasonable process control; the hot extrusion treatment further improves the internal structure and improves the mechanical properties in a specific direction; the machining adopts special methods to avoid adverse effects on material properties, ensuring that the precise size and accuracy requirements are met; and the surface treatment measures greatly enhance the surface quality, wear resistance and corrosion resistance of the brake disc, effectively extend the service life, and ensure the efficient and stable operation of the aerospace vehicle braking system. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The features and advantages of the present invention will be more clearly understood by referring to the accompanying drawings, which are schematic and should not be construed as limiting the present invention in any way. In the accompanying drawings: Figure 1 The present invention is a flow chart of the method for preparing the aviation copper-based static disk material. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0022] Based on the problem pointed out in the background technology that the existing copper-based stator disc materials have weak comprehensive performance, resulting in limited application in aviation brake systems, the present invention provides an aviation copper-based stator disc material and a preparation method thereof, aiming to significantly improve the comprehensive performance of the aviation copper-based stator disc material, such as strength, hardness, high-temperature wear resistance, friction coefficient stability and corrosion resistance, to meet the requirements of aviation brake systems, and is particularly suitable for applications under complex working conditions.

[0023] The aviation copper-based static disk material of the present invention comprises, by mass percentage, 55%-65% of high-purity electrolytic copper, 10%-15% of aluminum bronze alloy, 4%-8% of nano nickel powder, 2%-5% of chromium-molybdenum alloy, 2%-6% of nano silicon carbide particles, 1.5%-4% of continuous carbon fiber bundles, 1%-3% of hexagonal boron nitride nanosheets, 0.5%-2% of tungsten carbide particles, 0.5%-2% of multilayer graphene, 0.3%-1.5% of sodium molybdate, 0.5-1.5% of coupling agent, 0.2%-1% of nano lubricant and 0.1%-0.8% of antioxidant.

[0024] In the above, the purity of high-purity electrolytic copper is greater than or equal to 99%, and it is further preferred to use ultra-high-purity electrolytic copper with a purity of 99.9%.

[0025] In some preferred embodiments, the coupling agent includes 0.3%-0.9% of a silane coupling agent and 0.2%-0.6% of a titanate coupling agent, the nano-lubricant includes 0.1%-0.5% of nano-molybdenum disulfide and 0.1%-0.5% of nano-zinc borate, and the antioxidant includes 0.05%-0.4% of a hindered phenol antioxidant and 0.05%-0.4% of a phosphite antioxidant. Preferably, the hindered phenol antioxidant can be antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate). In the aviation copper-based static disk material, since the material works in a complex environment such as high temperature and high stress, it is easy to generate free radicals to initiate oxidation reactions. Antioxidant 1010 can effectively delay the oxidation process of the material. It reacts with free radicals through its own phenolic hydroxyl group to generate stable compounds, thereby interrupting the oxidation reaction and protecting the performance of the material. The phosphite antioxidant can be tris(2,4-di-tert-butylphenyl) phosphite. Tris(2,4-di-tert-butylphenyl) phosphate mainly plays the role of decomposing hydroperoxides, and works in conjunction with the main antioxidant. During the oxidation process, hydroperoxides will be produced in the material, and phosphite antioxidants can decompose them into harmless alcohols, ketones and other compounds, thereby reducing the possibility of further oxidation reactions caused by hydroperoxides. When used in conjunction with hindered phenol antioxidants, it can greatly improve the antioxidant properties of the material and extend the service life of the static disk material. Of course, the antioxidant combination and its proportion configuration in the above examples are not restrictive, and other types and / or ratios of antioxidants can also be selected.

[0026] In terms of matrix strengthening, the aviation copper-based static disc material of the present invention uses high-purity electrolytic copper to provide good electrical conductivity, thermal conductivity and basic ductility, and the aluminum bronze alloy has improved strength, hardness, wear resistance and corrosion resistance after special treatment, which work together to build a solid matrix framework. Nano nickel powder is further integrated to strengthen the overall strength and corrosion resistance, and chromium-molybdenum alloy focuses on enhancing high-temperature strength and oxidation resistance, so that the material can effectively maintain structural stability and resist wear, deformation and oxidation damage in the complex stress and high temperature environment faced by aerospace brake discs, greatly extending the service life; for friction performance optimization, nano silicon carbide particles significantly improve the hardness and wear resistance of the material with their nano-sized uniform dispersion characteristics The continuous carbon fiber bundles stabilize the material structure and enhance the mechanical properties during the friction process with their high strength and toughness. The lubricity and high temperature resistance of hexagonal boron nitride nanosheets effectively reduce the friction coefficient and reduce wear. The high hardness of tungsten carbide particles provides additional wear resistance. The self-lubricating properties of multilayer graphene and the lubricating effect of the oxide formed by sodium molybdate at high temperature cooperate with each other to ensure stable and reliable tribological properties under different working conditions, maintain the consistency and accuracy of the braking effect, and reduce energy loss and component wear during braking. In terms of interface bonding and stability improvement, the silane coupling agent and the titanate coupling agent work synergistically. The silane coupling agent can effectively handle the interface between the copper-based alloy and some strengthening phases. Interface bonding, titanate coupling agent focuses on improving the compatibility of specific particles and copper-based alloys. The two together enhance the binding force between the components, promote the uniform dispersion of different phases in the matrix, prevent component separation, improve the overall uniformity and stability of the material, ensure the reliability and consistency of material performance, and at the same time facilitate the processing and molding of the material and reduce processing defects; from the perspective of lubrication and anti-wear synergy, nano-molybdenum disulfide relies on the sliding mechanism of the layered structure to exert its lubrication effect, and nano-zinc borate forms a glassy covering layer at high temperature to isolate, lubricate and prevent oxidation. The two complement each other at different temperature stages and friction processes. During the initial friction, nano-molybdenum disulfide quickly reduces friction, and nano-boron The acid zinc covering layer continues to play a role, jointly reducing the friction coefficient, reducing wear, effectively protecting the surface of the static disc material, and adapting to the complex and changeable working environment of aerospace brake discs; in addition, hindered phenol antioxidants terminate the reaction by capturing free radicals through phenolic hydroxyl groups during the propagation stage of the oxidation chain reaction, and phosphite antioxidants decompose hydroperoxides to cut off the source during the initiation stage of the oxidation reaction. The two work together to inhibit the occurrence and development of the oxidation reaction from different stages, greatly improving the antioxidant properties of the material, delaying the oxidation aging process of the material in the special environment of aerospace, ensuring the stable performance of the brake disc during long-term use, reducing the risk of failure due to oxidation, and improving the reliability and safety of the entire brake system.

[0027] Further preferably, the aviation copper-based static disk material of the present invention also includes 0.1%-0.5% by mass of the rare earth element yttrium. During the solidification process of the copper-based alloy, the yttrium element can serve as the core of heterogeneous nucleation to effectively refine the grains. This synergistically acts with the high-purity electrolytic copper and aluminum bronze alloy and other components in the matrix to further improve the strength and hardness of the material. For example, in the early stage of solidification, yttrium atoms will gather in the liquid alloy to form a large number of crystal nuclei. These crystal nuclei will inhibit the growth of the surrounding grains during the growth process, thereby reducing the grain size of the entire alloy, increasing the grain boundary area of ​​small grains, hindering dislocation movement, and further enhancing the mechanical properties of the material. Together with strengthening components such as nano-nickel powder and chromium-molybdenum alloy, the material's load-bearing capacity in a high-stress braking environment is improved. Yttrium can also react with oxygen to form stable oxides. These oxides can form a protective film on the surface of the material. During the warm braking process, this protective film works synergistically with antioxidants (hindered phenol antioxidants and phosphite antioxidants) to prevent oxygen from further diffusing into the material, thereby improving the material's antioxidant properties. At the same time, yttrium can also improve the material's thermal stability and reduce the softening and deformation of the material at high temperatures. When it works together with components with good high-temperature properties such as hexagonal boron nitride nanosheets and tungsten carbide particles, it can better maintain the material's dimensional stability and tribological properties under high-temperature braking environments. From the perspective of crystal plane bonding, yttrium can improve the interface bonding between the reinforcing phase and the copper-based alloy matrix. It can form chemical bonds or segregation at the interface to enhance the bonding strength of the interface. It works synergistically with silane coupling agents and titanate coupling agents to further improve the overall uniformity and stability of the material, prevent the reinforcing phase from falling off from the matrix during force application, and ensure the structural integrity of the material during friction.

[0028] like Figure 1 As shown, the preparation method of the aviation copper-based static disk material of the present invention comprises: S1: Pretreatment of high-purity electrolytic copper, aluminum bronze alloy, nano nickel powder, chromium-molybdenum alloy, nano silicon carbide particles, continuous carbon fiber bundles, hexagonal boron nitride nanosheets and tungsten carbide particles; Preferably, the above step S1 specifically includes: S11: High-purity electrolytic copper, aluminum bronze alloy, nano nickel powder and chromium-molybdenum alloy are placed in a vacuum induction melting furnace for vacuum induction melting. The melting temperature is 1300-1500℃ and the melting time is 3-5 hours. During the vacuum induction melting process, the metal alloy is treated by combining electromagnetic stirring and ultrasonic treatment to ensure uniform composition. The melt is then poured into a water-cooled copper mold and rapidly cooled to room temperature to obtain a copper-based alloy ingot. This rapid cooling method helps to refine the grains and improve the strength and hardness of the material. The copper-based alloy ingot is then subjected to multiple hot rolling processes at a hot rolling temperature of 850-1000℃ and a reduction rate of 30%-50% for each process. During the hot rolling process, the thickness of the ingot is gradually reduced, which refines the internal grains of the alloy and improves the organizational structure. The hot-rolled plate is annealed Treatment, annealing temperature is 550-700℃, time is 3-5 hours, annealing is used to eliminate the internal stress generated during hot rolling, so that the organizational structure of the material is more stable, the annealed copper-based alloy plate is mechanically crushed, a jaw crusher is used to break the plate into small pieces with a side length of 3-5 cm, and the size is further reduced by milling. The milling speed is set to 100-200 m / min, and the feed rate is 0.1-0.3 mm / rev. The small pieces are processed into particles with a particle size of 1-3 mm. If the particle uniformity is insufficient or the particle size is not fine enough, ball milling treatment can be performed. The ball milling medium is stainless steel ball, the ball-to-material ratio is (5-8):1, the ball milling time is 6-10 hours, and the ball milling speed is 200-300 rpm. Through the collision and friction between the ball milling medium and the alloy particles, the alloy particles are gradually refined to 10-50 microns; S12: Soaking the nano-SiC particles in a dopamine solution, wherein the concentration of the dopamine solution is 2-4 g / L and the pH value is 8-9, and reacting the solution under stirring at room temperature for 24-48 hours, i.e., forming a polydopamine coating on the surface of the nano-SiC particles by self-polymerization of dopamine to improve the bonding between the nano-SiC particles and the copper-based alloy. The coating formed by self-polymerization of dopamine under alkaline conditions has good adhesion and active groups, and can enhance the chemical bonding between the nano-SiC particles and the copper-based alloy. Then, taking out the nano-SiC particles, rinsing them with deionized water, and drying them at 80-100° C. for 4-6 hours. S13: Plasma treatment is performed on the continuous carbon fiber bundle to improve its surface activity. The treatment time is 1-2 hours and the power is 500-1000W. Then, the continuous carbon fiber bundle is impregnated with a silane coupling agent. The treatment time is 2-4 hours and the temperature is 60-80°C. The treated continuous carbon fiber bundle is dried at 100-120°C for 3-5 hours. These two-step treatment can introduce active groups on the surface of the continuous carbon fiber and improve its compatibility with the copper-based alloy, so that the carbon fiber can be better integrated into the copper-based alloy system to play its reinforcing role. S14: soaking the hexagonal boron nitride nanosheets in a sodium hydroxide solution with a concentration of 1-2 mol / L, stirring the reaction at 80-100°C for 2-4 hours, then rinsing with deionized water until neutral, drying at 100-120°C for 4-6 hours, and then modifying with a silane coupling agent for 2-4 hours at a temperature of 60-80°C. The hexagonal boron nitride nanosheets are first hydroxylated in a sodium hydroxide solution to increase the surface active groups, and then modified with a silane coupling agent to improve the compatibility with the copper-based alloy, which is beneficial to its uniform dispersion in the alloy and good bonding with the matrix; S15: The tungsten carbide particles are ball-milled, the ball-milling medium is zirconium oxide balls, the ball-to-material ratio is (8-12):1, the ball-milling time is 15-20 hours, and the ball-milled tungsten carbide particles are dried at 80-100°C for 4-6 hours. The ball-milling treatment of tungsten carbide particles can refine the particle size, increase its specific surface area, and improve its dispersibility and activity in copper-based alloys, thereby better playing the role of enhancing wear resistance.

[0029] S2: adding the pretreated high-purity electrolytic copper, aluminum bronze alloy, nano nickel powder, chromium-molybdenum alloy, nano silicon carbide particles, continuous carbon fiber bundles, hexagonal boron nitride nanosheets and tungsten carbide particles, multilayer graphene, sodium molybdate, coupling agent, nano lubricant and antioxidant into a high-energy ball mill for ball milling treatment; if the components of the static disk material of the present invention contain rare earth element yttrium, it is also added in this step; Preferably, in the above step S2, the rotation speed of the high-energy ball mill is 300-500 r / min, and the ball milling time is 6-10 hours. During the ball milling process, a dispersant (such as ethanol or acetone) is added to prevent powder agglomeration, and then the powder after ball milling is vacuum dried at a drying temperature of 80-100° C. for 4-6 hours.

[0030] S3: loading the mixed powder into a mold, and then placing the mold in a hot isostatic pressing device for hot isostatic pressing; Preferably, in the above step S3, the temperature of hot isostatic pressing is 800-1000°C, the pressure is 150-200 MPa, and the holding time is 2-4 hours. Hot isostatic pressing can make the density of the material reach more than 99%.

[0031] S4: placing the formed green body into a vacuum sintering furnace and sintering it in a staged heating manner, and then performing hot extrusion treatment; Preferably, in the above step S4, the vacuum sintering furnace is first heated to 600-800°C at a rate of 5-10°C / min, kept at this temperature for 1-2 hours, and then heated to a sintering temperature of 1000-1200°C at a rate of 3-5°C / min, kept at this temperature for 3-4 hours to avoid cracking of the material caused by a sudden temperature rise. The vacuum degree of the vacuum sintering furnace is 1×10 -4 -1×10 -3 Pa, the temperature of hot extrusion treatment is 750-900℃, and the extrusion ratio is (15-25):1 to further improve the density of the material.

[0032] S5: Mechanically process and surface treat the sintered copper-based static disk material; Preferably, in the above step S5, the machining can be performed by CNC machining center for turning, milling, drilling and other machining operations to ensure that the material reaches the size and precision required by the design. During the machining process, low temperature machining and micro-cutting are used to avoid excessive heat and stress. The surface treatment method is: the surface is subjected to aluminum oxide sandblasting at a pressure of 0.3-0.6MPa, and the processing particle size is 20-40 mesh. Then, a wear-resistant coating, such as a WC-Co ceramic coating, is sprayed. For example, a thermal spraying process, such as high-speed flame spraying (HVOF), is used. During spraying, the gas flow rate is controlled at 150-250 liters / minute, the oxygen flow rate is controlled at 400-600 liters / minute, and the powder feeding rate is 30-50 grams / minute, so that the coating is evenly deposited on the surface of the static disk assembly. The coating thickness is controlled at 0.05-0.2 mm. Then, the static disk material is placed in a vacuum chamber of the ion implantation equipment and evacuated to 1×10 -4 -1×10 -3 Pa, nitrogen ion implantation was performed, the energy of the implanted nitrogen ions was 50-100 keV, and the dose was During the implantation process, the ion beam current density is controlled to be 5-10μA / cm 2 To ensure that the ions are evenly implanted into the surface of the static disk to a certain depth, thereby improving the surface hardness, wear resistance and corrosion resistance.

[0033] In the preparation method of the present invention, vacuum sintering further densifies the formed green body and forms a stable organizational structure and phase composition, and the subsequent hot extrusion treatment further improves the internal organizational structure of the material on this basis. The sintered material has some pores or the grain structure is not ideal. During the hot extrusion process, the material has good plastic deformation ability at high temperature. Through extrusion, the material forms a certain texture along the extrusion direction, and the grains are further refined and oriented, which further improves the density and performance of the material, improves the strength and improves the anisotropy. This synergistic effect enables the material to better adapt to the use requirements of aerospace brake discs under complex forces and working conditions, and improves its reliability and durability. The surface treatment step after machining has a positive effect on the surface microstructure of the material. Sandblasting makes the surface form a certain degree of roughness, increases the active sites and specific surface area of ​​the surface, and the coating material can better adhere to the surface when spraying the wear-resistant coating, and a good bonding interface is formed between the coating and the substrate. The WC particles in the WC-Co ceramic coating form a dense wear-resistant layer on the surface. The Co element will play a certain bonding and diffusion role at the interface between the coating and the substrate, improving the adhesion of the coating. Ion implantation forms an ion implantation layer of a certain depth on the surface, which changes the atomic structure and chemical bonding state of the surface, increases the surface hardness, and enhances the resistance to wear and corrosion at the microscopic level. This improvement in the surface microstructure can reduce the fluctuation of the friction coefficient, reduce the wear rate, and improve the corrosion resistance of the material during the braking process of the aerospace brake disc, thereby extending the service life of the brake disc and ensuring the stability and safety of braking.

[0034] The technical solution of the present invention is further described below in conjunction with a plurality of embodiments and comparative examples.

[0035] Embodiment 1 The aviation copper-based static disk materials measured by mass percentage include: 64% high-purity electrolytic copper, 14% aluminum bronze alloy, 6% nano-nickel powder, 3% chromium-molybdenum alloy, 4% nano-silicon carbide particles, 2% continuous carbon fiber bundles, 2% hexagonal boron nitride nanosheets, 1% tungsten carbide particles, 1% multilayer graphene, 1% sodium molybdate, 0.6% silane coupling agent, 0.4% titanate coupling agent, 0.3% nano-molybdenum disulfide, 0.3% nano-zinc borate, 0.2% hindered phenol antioxidant and 0.2% phosphite antioxidant.

[0036] The preparation method of aviation copper-based static disk material includes: High-purity electrolytic copper, aluminum bronze alloy, nano nickel powder and chromium-molybdenum alloy are placed in a vacuum induction melting furnace for vacuum induction melting at a melting temperature of 1300°C and a melting time of 3 hours. During the vacuum induction melting process, the metal alloy is treated by a combination of electromagnetic stirring and ultrasonic treatment. The melt is then poured into a water-cooled copper mold and rapidly cooled to room temperature to obtain a copper-based alloy ingot. The copper-based alloy ingot is then subjected to multiple hot rolling treatments at a hot rolling temperature of 850°C. The hot-rolled plate is annealed at a temperature of 550°C for 3 hours. The annealed copper-based alloy plate is mechanically crushed by a jaw crusher to break the plate into small pieces. The small pieces are processed into particles by milling and ball milling is performed. The ball milling medium is stainless steel balls with a ball-to-material ratio of 5:1. The ball milling time is 6 hours and the ball milling speed is 200 rpm. The nano silicon carbide particles are immersed in a dopamine solution. The concentration of the dopamine solution is The concentration of the carbon fiber is 2g / L, the pH value is 8, and the reaction is stirred at room temperature for 24 hours, then the nano silicon carbide particles are taken out and rinsed with deionized water, and dried at 80°C for 4 hours; the continuous carbon fiber bundle is plasma treated for 1 hour at a power of 500W, and then impregnated with a silane coupling agent for 2 hours at a temperature of 60°C, and the treated continuous carbon fiber bundle is dried at 100°C for 3 hours; the hexagonal boron nitride nanosheets are immersed in a sodium hydroxide solution with a concentration of 1mol / L, stirred at 80°C for 2 hours, then rinsed with deionized water to neutrality, dried at 100°C for 4 hours, and then modified with a silane coupling agent for 2 hours at a temperature of 60°C; the tungsten carbide particles are ball-milled, the ball-milling medium is zirconium oxide balls, the ball-to-material ratio is 8:1, the ball-milling time is 15 hours, and the ball-milled tungsten carbide particles are dried at 80°C for 4 hours.

[0037] The pretreated high-purity electrolytic copper, aluminum bronze alloy, nano-nickel powder, chromium-molybdenum alloy, nano-silicon carbide particles, continuous carbon fiber bundles, hexagonal boron nitride nanosheets and tungsten carbide particles, as well as multilayer graphene, sodium molybdate, coupling agent, nano-lubricant and antioxidant are added to a high-energy ball mill for ball milling. The ball milling speed of the high-energy ball mill is 300 r / min, and the ball milling time is 6 hours. During the ball milling process, acetone is added, and then the ball-milled powder is vacuum dried at a drying temperature of 80°C for 4 hours.

[0038] The mixed powder is loaded into a mold, and then the mold is placed in a hot isostatic pressing device for hot isostatic pressing processing. The hot isostatic pressing temperature is 800° C., the pressure is 150 MPa, and the holding time is 2 hours.

[0039] The formed green body was placed in a vacuum sintering furnace. The temperature of the vacuum sintering furnace was first raised to 600°C at a rate of 5°C / min, kept at this temperature for 1 hour, and then raised to 1000°C at a rate of 3°C / min, kept at this temperature for 3 hours. The vacuum degree of the vacuum sintering furnace was 1×10 -4 Pa, and then hot extrusion treatment is performed, the hot extrusion temperature is 750°C, and the extrusion ratio is 15:1.

[0040] The sintered copper-based static disk material was machined, and the surface was treated with aluminum oxide sandblasting at a pressure of 0.3 MPa with a particle size of 40 mesh. Then, the WC-Co ceramic coating was sprayed on the material surface by high-speed flame spraying. The gas flow rate was controlled at 150 liters / minute, the oxygen flow rate was controlled at 400 liters / minute, and the powder feeding rate was 30 grams / minute. Then, the static disk material was placed in the vacuum chamber of the ion implantation equipment and evacuated to 1×10 -4 Pa, nitrogen ion implantation was performed with an energy of 50 keV and a dose of During the implantation process, the ion beam current density was controlled to be 5μA / cm².

[0041] Embodiment 2 The aviation copper-based static disk materials measured by mass percentage include: 64% high-purity electrolytic copper, 14% aluminum bronze alloy, 6% nano-nickel powder, 3% chromium-molybdenum alloy, 4% nano-silicon carbide particles, 2% continuous carbon fiber bundles, 2% hexagonal boron nitride nanosheets, 1% tungsten carbide particles, 1% multilayer graphene, 1% sodium molybdate, 0.6% silane coupling agent, 0.4% titanate coupling agent, 0.3% nano-molybdenum disulfide, 0.3% nano-zinc borate, 0.2% hindered phenol antioxidant and 0.2% phosphite antioxidant.

[0042] The preparation method of aviation copper-based static disk material includes: High-purity electrolytic copper, aluminum bronze alloy, nano nickel powder and chromium-molybdenum alloy are placed in a vacuum induction melting furnace for vacuum induction melting. The melting temperature is 1400°C and the melting time is 4 hours. During the vacuum induction melting process, the metal alloy is treated by combining electromagnetic stirring and ultrasonic treatment. The melt is then poured into a water-cooled copper mold and quickly cooled to room temperature to obtain a copper-based alloy ingot. The copper-based alloy ingot is then subjected to multiple hot rolling treatments at a hot rolling temperature of 900°C. The hot-rolled plate is annealed at an annealing temperature of 600°C for 4 hours. The annealed copper-based alloy plate is mechanically crushed using a jaw crusher to break the plate into small pieces. The small pieces are processed into particles by milling and ball milling is performed. The ball milling medium is stainless steel balls, the ball-to-material ratio is 6:1, the ball milling time is 8 hours, and the ball milling speed is 250 rpm. The nano silicon carbide particles are immersed in a dopamine solution, and the concentration of the dopamine solution is 3g / L, pH value is 8.5, stirring reaction at room temperature for 36 hours, then taking out the nano silicon carbide particles and rinsing them with deionized water, and drying them at 90 ℃ for 5 hours; the continuous carbon fiber bundle is plasma treated for 1.5 hours, the power is 800W, and then impregnated with a silane coupling agent for 3 hours at a temperature of 70 ℃, and the treated continuous carbon fiber bundle is dried at 110 ℃ for 4 hours; the hexagonal boron nitride nanosheets are immersed in a sodium hydroxide solution with a concentration of 1.5 mol / L, stirred and reacted at 90 ℃ for 3 hours, then rinsed with deionized water to neutrality, dried at 110 ℃ for 5 hours, and then modified with a silane coupling agent for 3 hours at a temperature of 70 ℃; the tungsten carbide particles are ball-milled, the ball-milling medium is zirconium oxide balls, the ball-to-material ratio is 10:1, the ball-milling time is 18 hours, and the ball-milled tungsten carbide particles are dried at 90 ℃ for 5 hours.

[0043] The pretreated high-purity electrolytic copper, aluminum bronze alloy, nano-nickel powder, chromium-molybdenum alloy, nano-silicon carbide particles, continuous carbon fiber bundles, hexagonal boron nitride nanosheets and tungsten carbide particles, as well as multilayer graphene, sodium molybdate, coupling agent, nano-lubricant and antioxidant are added to a high-energy ball mill for ball milling. The ball milling speed of the high-energy ball mill is 400r / min, and the ball milling time is 8 hours. During the ball milling process, acetone is added, and then the ball-milled powder is vacuum dried at a drying temperature of 90°C for 5 hours.

[0044] The mixed powder is loaded into a mold, and then the mold is placed in a hot isostatic pressing device for hot isostatic pressing. The hot isostatic pressing temperature is 900° C., the pressure is 180 MPa, and the holding time is 3 hours.

[0045] The formed green body was placed in a vacuum sintering furnace. The temperature of the vacuum sintering furnace was first raised to 700°C at a rate of 8°C / min, kept at this temperature for 1.5 hours, and then raised to 1100°C at a rate of 4°C / min, kept at this temperature for 3.5 hours. The vacuum degree of the vacuum sintering furnace was 5×10 -4 Pa, and then hot extrusion treatment is performed, the hot extrusion temperature is 800°C, and the extrusion ratio is 20:1.

[0046] The sintered copper-based static disk material was machined, and the surface was treated with aluminum oxide sandblasting at a pressure of 0.5 MPa with a particle size of 40 mesh. Then, the WC-Co ceramic coating was sprayed on the material surface by high-speed flame spraying. The gas flow rate was controlled at 200 liters / minute, the oxygen flow rate was controlled at 500 liters / minute, and the powder feeding rate was 40 grams / minute. Then, the static disk material was placed in the vacuum chamber of the ion implantation equipment and evacuated to 5×10 -4 Pa, nitrogen ion implantation was performed, the energy of the implanted nitrogen ions was 80 keV, and the dose was During the implantation process, the ion beam current density was controlled to be 8μA / cm².

[0047] Embodiment 3 The aviation copper-based static disk materials measured by mass percentage include: 64% high-purity electrolytic copper, 14% aluminum bronze alloy, 6% nano-nickel powder, 3% chromium-molybdenum alloy, 4% nano-silicon carbide particles, 2% continuous carbon fiber bundles, 2% hexagonal boron nitride nanosheets, 1% tungsten carbide particles, 1% multilayer graphene, 1% sodium molybdate, 0.6% silane coupling agent, 0.4% titanate coupling agent, 0.3% nano-molybdenum disulfide, 0.3% nano-zinc borate, 0.2% hindered phenol antioxidant and 0.2% phosphite antioxidant.

[0048] The preparation method of aviation copper-based static disk material includes: High-purity electrolytic copper, aluminum bronze alloy, nano nickel powder and chromium-molybdenum alloy are placed in a vacuum induction melting furnace for vacuum induction melting at a melting temperature of 1500°C and a melting time of 5 hours. During the vacuum induction melting process, the metal alloy is treated by a combination of electromagnetic stirring and ultrasonic treatment. The melt is then poured into a water-cooled copper mold and rapidly cooled to room temperature to obtain a copper-based alloy ingot. The copper-based alloy ingot is then subjected to multiple hot rolling treatments at a hot rolling temperature of 1000°C. The hot-rolled plate is annealed at a temperature of 700°C for 5 hours. The annealed copper-based alloy plate is mechanically crushed by a jaw crusher to break the plate into small pieces. The small pieces are processed into particles by milling and ball milling is performed. The ball milling medium is stainless steel balls, the ball-to-material ratio is 8:1, the ball milling time is 10 hours, and the ball milling speed is 300 rpm. The nano silicon carbide particles are immersed in a dopamine solution. The concentration of the dopamine solution is 4g / L, pH value is 9, stirring reaction at room temperature for 48 hours, then taking out the nano silicon carbide particles and rinsing them with deionized water, and drying them at 100 ℃ for 6 hours; the continuous carbon fiber bundle is plasma treated for 2 hours, the power is 1000W, and then impregnated with a silane coupling agent for 4 hours at a temperature of 80 ℃, and the treated continuous carbon fiber bundle is dried at 120 ℃ for 5 hours; the hexagonal boron nitride nanosheets are immersed in a sodium hydroxide solution with a concentration of 2mol / L, stirred and reacted at 100 ℃ for 4 hours, then rinsed with deionized water to neutrality, dried at 120 ℃ for 6 hours, and then modified with a silane coupling agent for 4 hours at a temperature of 80 ℃; the tungsten carbide particles are ball milled, the ball milling medium is zirconium oxide balls, the ball-to-material ratio is 12:1, the ball milling time is 20 hours, and the ball-milled tungsten carbide particles are dried at 100 ℃ for 6 hours.

[0049] The pretreated high-purity electrolytic copper, aluminum bronze alloy, nano-nickel powder, chromium-molybdenum alloy, nano-silicon carbide particles, continuous carbon fiber bundles, hexagonal boron nitride nanosheets and tungsten carbide particles, as well as multilayer graphene, sodium molybdate, coupling agent, nano-lubricant and antioxidant are added to a high-energy ball mill for ball milling. The ball milling speed of the high-energy ball mill is 500r / min, and the ball milling time is 10 hours. During the ball milling process, acetone is added, and then the ball-milled powder is vacuum dried at a drying temperature of 100°C for 6 hours.

[0050] The mixed powder is loaded into a mold, and then the mold is placed in a hot isostatic pressing device for hot isostatic pressing processing. The hot isostatic pressing temperature is 1000° C., the pressure is 200 MPa, and the holding time is 4 hours.

[0051] The formed green body was placed in a vacuum sintering furnace. The temperature of the vacuum sintering furnace was first raised to 800°C at a rate of 10°C / min and kept at this temperature for 2 hours. Then the temperature was raised to 1200°C at a rate of 5°C / min and kept at this temperature for 4 hours. The vacuum degree of the vacuum sintering furnace was 1×10 -3 Pa, and then hot extrusion treatment is performed, the hot extrusion temperature is 900°C, and the extrusion ratio is 25:1.

[0052] The sintered copper-based static disk material was machined, and the surface was treated with aluminum oxide sandblasting at a pressure of 0.6 MPa with a particle size of 40 mesh. Then, the WC-Co ceramic coating was sprayed on the material surface by high-speed flame spraying. The gas flow rate was controlled at 250 liters / minute, the oxygen flow rate was controlled at 600 liters / minute, and the powder feeding rate was 50 grams / minute. Then, the static disk material was placed in the vacuum chamber of the ion implantation equipment and evacuated to 1×10 -3 Pa, nitrogen ion implantation was performed, the energy of the implanted nitrogen ions was 100 keV, and the dose was During the implantation process, the ion beam current density was controlled to be 10μA / cm².

[0053] Embodiment 4 The aviation copper-based static disk materials measured by mass percentage include: 60% high-purity electrolytic copper, 12% aluminum bronze alloy, 7% nano-nickel powder, 5% chromium-molybdenum alloy, 5% nano-silicon carbide particles, 4% continuous carbon fiber bundles, 1.5% hexagonal boron nitride nanosheets, 1.5% tungsten carbide particles, 1.5% multilayer graphene, 0.8% sodium molybdate, 0.5% silane coupling agent, 0.3% titanate coupling agent, 0.2% nano-molybdenum disulfide, 0.2% nano-zinc borate, 0.3% hindered phenol antioxidant and 0.2% phosphite antioxidant.

[0054] The preparation method of aviation copper-based static disk material includes: High-purity electrolytic copper, aluminum bronze alloy, nano nickel powder and chromium-molybdenum alloy are placed in a vacuum induction melting furnace for vacuum induction melting at a melting temperature of 1300°C and a melting time of 3 hours. During the vacuum induction melting process, the metal alloy is treated by a combination of electromagnetic stirring and ultrasonic treatment. The melt is then poured into a water-cooled copper mold and rapidly cooled to room temperature to obtain a copper-based alloy ingot. The copper-based alloy ingot is then subjected to multiple hot rolling treatments at a hot rolling temperature of 850°C. The hot-rolled plate is annealed at a temperature of 550°C for 3 hours. The annealed copper-based alloy plate is mechanically crushed by a jaw crusher to break the plate into small pieces. The small pieces are processed into particles by milling and ball milling is performed. The ball milling medium is stainless steel balls with a ball-to-material ratio of 5:1. The ball milling time is 6 hours and the ball milling speed is 200 rpm. The nano silicon carbide particles are immersed in a dopamine solution. The concentration of the dopamine solution is The concentration of the carbon fiber is 2g / L, the pH value is 8, and the reaction is stirred at room temperature for 24 hours, then the nano silicon carbide particles are taken out and rinsed with deionized water, and dried at 80°C for 4 hours; the continuous carbon fiber bundle is plasma treated for 1 hour at a power of 500W, and then impregnated with a silane coupling agent for 2 hours at a temperature of 60°C, and the treated continuous carbon fiber bundle is dried at 100°C for 3 hours; the hexagonal boron nitride nanosheets are immersed in a sodium hydroxide solution with a concentration of 1mol / L, stirred at 80°C for 2 hours, then rinsed with deionized water to neutrality, dried at 100°C for 4 hours, and then modified with a silane coupling agent for 2 hours at a temperature of 60°C; the tungsten carbide particles are ball-milled, the ball-milling medium is zirconium oxide balls, the ball-to-material ratio is 8:1, the ball-milling time is 15 hours, and the ball-milled tungsten carbide particles are dried at 80°C for 4 hours.

[0055] The pretreated high-purity electrolytic copper, aluminum bronze alloy, nano-nickel powder, chromium-molybdenum alloy, nano-silicon carbide particles, continuous carbon fiber bundles, hexagonal boron nitride nanosheets and tungsten carbide particles, as well as multilayer graphene, sodium molybdate, coupling agent, nano-lubricant and antioxidant are added to a high-energy ball mill for ball milling. The ball milling speed of the high-energy ball mill is 300 r / min, and the ball milling time is 6 hours. During the ball milling process, acetone is added, and then the ball-milled powder is vacuum dried at a drying temperature of 80°C for 4 hours.

[0056] The mixed powder is loaded into a mold, and then the mold is placed in a hot isostatic pressing device for hot isostatic pressing processing. The hot isostatic pressing temperature is 800° C., the pressure is 150 MPa, and the holding time is 2 hours.

[0057] The formed green body was placed in a vacuum sintering furnace. The temperature of the vacuum sintering furnace was first raised to 600°C at a rate of 5°C / min, kept at this temperature for 1 hour, and then raised to 1000°C at a rate of 3°C / min, kept at this temperature for 3 hours. The vacuum degree of the vacuum sintering furnace was 1×10 -4 Pa, and then hot extrusion treatment is performed, the hot extrusion temperature is 750°C, and the extrusion ratio is 15:1.

[0058] The sintered copper-based static disk material was machined, and the surface was treated with aluminum oxide sandblasting at a pressure of 0.3 MPa with a particle size of 40 mesh. Then, the WC-Co ceramic coating was sprayed on the material surface by high-speed flame spraying. The gas flow rate was controlled at 150 liters / minute, the oxygen flow rate was controlled at 400 liters / minute, and the powder feeding rate was 30 grams / minute. Then, the static disk material was placed in the vacuum chamber of the ion implantation equipment and evacuated to 1×10 -4 Pa, nitrogen ion implantation was performed with an energy of 50 keV and a dose of During the implantation process, the ion beam current density was controlled to be 5μA / cm².

[0059] Embodiment 5 The aviation copper-based static disk materials measured by mass percentage include: 60% high-purity electrolytic copper, 12% aluminum bronze alloy, 7% nano-nickel powder, 5% chromium-molybdenum alloy, 5% nano-silicon carbide particles, 4% continuous carbon fiber bundles, 1.5% hexagonal boron nitride nanosheets, 1.5% tungsten carbide particles, 1.5% multilayer graphene, 0.8% sodium molybdate, 0.5% silane coupling agent, 0.3% titanate coupling agent, 0.2% nano-molybdenum disulfide, 0.2% nano-zinc borate, 0.3% hindered phenol antioxidant and 0.2% phosphite antioxidant.

[0060] The preparation method of aviation copper-based static disk material includes: High-purity electrolytic copper, aluminum bronze alloy, nano nickel powder and chromium-molybdenum alloy are placed in a vacuum induction melting furnace for vacuum induction melting. The melting temperature is 1400°C and the melting time is 4 hours. During the vacuum induction melting process, the metal alloy is treated by combining electromagnetic stirring and ultrasonic treatment. The melt is then poured into a water-cooled copper mold and quickly cooled to room temperature to obtain a copper-based alloy ingot. The copper-based alloy ingot is then subjected to multiple hot rolling treatments at a hot rolling temperature of 900°C. The hot-rolled plate is annealed at an annealing temperature of 600°C for 4 hours. The annealed copper-based alloy plate is mechanically crushed using a jaw crusher to break the plate into small pieces. The small pieces are processed into particles by milling and ball milling is performed. The ball milling medium is stainless steel balls, the ball-to-material ratio is 6:1, the ball milling time is 8 hours, and the ball milling speed is 250 rpm. The nano silicon carbide particles are immersed in a dopamine solution, and the concentration of the dopamine solution is 3g / L, pH value is 8.5, stirring reaction at room temperature for 36 hours, then taking out the nano silicon carbide particles and rinsing them with deionized water, and drying them at 90 ℃ for 5 hours; the continuous carbon fiber bundle is plasma treated for 1.5 hours, the power is 800W, and then impregnated with a silane coupling agent for 3 hours at a temperature of 70 ℃, and the treated continuous carbon fiber bundle is dried at 110 ℃ for 4 hours; the hexagonal boron nitride nanosheets are immersed in a sodium hydroxide solution with a concentration of 1.5 mol / L, stirred and reacted at 90 ℃ for 3 hours, then rinsed with deionized water to neutrality, dried at 110 ℃ for 5 hours, and then modified with a silane coupling agent for 3 hours at a temperature of 70 ℃; the tungsten carbide particles are ball-milled, the ball-milling medium is zirconium oxide balls, the ball-to-material ratio is 10:1, the ball-milling time is 18 hours, and the ball-milled tungsten carbide particles are dried at 90 ℃ for 5 hours.

[0061] The pretreated high-purity electrolytic copper, aluminum bronze alloy, nano-nickel powder, chromium-molybdenum alloy, nano-silicon carbide particles, continuous carbon fiber bundles, hexagonal boron nitride nanosheets and tungsten carbide particles, as well as multilayer graphene, sodium molybdate, coupling agent, nano-lubricant and antioxidant are added to a high-energy ball mill for ball milling. The ball milling speed of the high-energy ball mill is 400r / min, and the ball milling time is 8 hours. During the ball milling process, acetone is added, and then the ball-milled powder is vacuum dried at a drying temperature of 90°C for 5 hours.

[0062] The mixed powder is loaded into a mold, and then the mold is placed in a hot isostatic pressing device for hot isostatic pressing. The hot isostatic pressing temperature is 900° C., the pressure is 180 MPa, and the holding time is 3 hours.

[0063] The formed green body was placed in a vacuum sintering furnace. The temperature of the vacuum sintering furnace was first raised to 700°C at a rate of 8°C / min, kept at this temperature for 1.5 hours, and then raised to 1100°C at a rate of 4°C / min, kept at this temperature for 3.5 hours. The vacuum degree of the vacuum sintering furnace was 5×10 -4 Pa, and then hot extrusion treatment is performed, the hot extrusion temperature is 800°C, and the extrusion ratio is 20:1.

[0064] The sintered copper-based static disk material was machined, and the surface was treated with aluminum oxide sandblasting at a pressure of 0.5 MPa with a particle size of 40 mesh. Then, the WC-Co ceramic coating was sprayed on the material surface by high-speed flame spraying. The gas flow rate was controlled at 200 liters / minute, the oxygen flow rate was controlled at 500 liters / minute, and the powder feeding rate was 40 grams / minute. Then, the static disk material was placed in the vacuum chamber of the ion implantation equipment and evacuated to 5×10 -4 Pa, nitrogen ion implantation was performed, the energy of the implanted nitrogen ions was 80 keV, and the dose was During the implantation process, the ion beam current density was controlled to be 8μA / cm².

[0065] Embodiment 6 The aviation copper-based static disk materials measured by mass percentage include: 60% high-purity electrolytic copper, 12% aluminum bronze alloy, 7% nano-nickel powder, 5% chromium-molybdenum alloy, 5% nano-silicon carbide particles, 4% continuous carbon fiber bundles, 1.5% hexagonal boron nitride nanosheets, 1.5% tungsten carbide particles, 1.5% multilayer graphene, 0.8% sodium molybdate, 0.5% silane coupling agent, 0.3% titanate coupling agent, 0.2% nano-molybdenum disulfide, 0.2% nano-zinc borate, 0.3% hindered phenol antioxidant and 0.2% phosphite antioxidant.

[0066] The preparation method of aviation copper-based static disk material includes: High-purity electrolytic copper, aluminum bronze alloy, nano nickel powder and chromium-molybdenum alloy are placed in a vacuum induction melting furnace for vacuum induction melting at a melting temperature of 1500°C and a melting time of 5 hours. During the vacuum induction melting process, the metal alloy is treated by a combination of electromagnetic stirring and ultrasonic treatment. The melt is then poured into a water-cooled copper mold and rapidly cooled to room temperature to obtain a copper-based alloy ingot. The copper-based alloy ingot is then subjected to multiple hot rolling treatments at a hot rolling temperature of 1000°C. The hot-rolled plate is annealed at a temperature of 700°C for 5 hours. The annealed copper-based alloy plate is mechanically crushed by a jaw crusher to break the plate into small pieces. The small pieces are processed into particles by milling and ball milling is performed. The ball milling medium is stainless steel balls, the ball-to-material ratio is 8:1, the ball milling time is 10 hours, and the ball milling speed is 300 rpm. The nano silicon carbide particles are immersed in a dopamine solution. The concentration of the dopamine solution is 4g / L, pH value is 9, stirring reaction at room temperature for 48 hours, then taking out the nano silicon carbide particles and rinsing them with deionized water, and drying them at 100 ℃ for 6 hours; the continuous carbon fiber bundle is plasma treated for 2 hours, the power is 1000W, and then impregnated with a silane coupling agent for 4 hours at a temperature of 80 ℃, and the treated continuous carbon fiber bundle is dried at 120 ℃ for 5 hours; the hexagonal boron nitride nanosheets are immersed in a sodium hydroxide solution with a concentration of 2mol / L, stirred and reacted at 100 ℃ for 4 hours, then rinsed with deionized water to neutrality, dried at 120 ℃ for 6 hours, and then modified with a silane coupling agent for 4 hours at a temperature of 80 ℃; the tungsten carbide particles are ball milled, the ball milling medium is zirconium oxide balls, the ball-to-material ratio is 12:1, the ball milling time is 20 hours, and the ball-milled tungsten carbide particles are dried at 100 ℃ for 6 hours.

[0067] The pretreated high-purity electrolytic copper, aluminum bronze alloy, nano-nickel powder, chromium-molybdenum alloy, nano-silicon carbide particles, continuous carbon fiber bundles, hexagonal boron nitride nanosheets and tungsten carbide particles, as well as multilayer graphene, sodium molybdate, coupling agent, nano-lubricant and antioxidant are added to a high-energy ball mill for ball milling. The ball milling speed of the high-energy ball mill is 500r / min, and the ball milling time is 10 hours. During the ball milling process, acetone is added, and then the ball-milled powder is vacuum dried at a drying temperature of 100°C for 6 hours.

[0068] The mixed powder is loaded into a mold, and then the mold is placed in a hot isostatic pressing device for hot isostatic pressing processing. The hot isostatic pressing temperature is 1000° C., the pressure is 200 MPa, and the holding time is 4 hours.

[0069] The formed green body was placed in a vacuum sintering furnace. The temperature of the vacuum sintering furnace was first raised to 800°C at a rate of 10°C / min and kept at this temperature for 2 hours. Then the temperature was raised to 1200°C at a rate of 5°C / min and kept at this temperature for 4 hours. The vacuum degree of the vacuum sintering furnace was 1×10 -3 Pa, and then hot extrusion treatment is performed, the hot extrusion temperature is 900°C, and the extrusion ratio is 25:1.

[0070] The sintered copper-based static disk material was machined, and the surface was treated with aluminum oxide sandblasting at a pressure of 0.6 MPa with a particle size of 40 mesh. Then, the WC-Co ceramic coating was sprayed on the material surface by high-speed flame spraying. The gas flow rate was controlled at 250 liters / minute, the oxygen flow rate was controlled at 600 liters / minute, and the powder feeding rate was 50 grams / minute. Then, the static disk material was placed in the vacuum chamber of the ion implantation equipment and evacuated to 1×10 -3 Pa, nitrogen ion implantation was performed, the energy of the implanted nitrogen ions was 100 keV, and the dose was During the implantation process, the ion beam current density was controlled to be 10μA / cm².

[0071] Comparative Example 1 Material components: electrolytic copper 68%, aluminum bronze alloy 18%, micron-grade nickel powder 4%, chromium-molybdenum alloy 4%, nano silicon carbide particles 2%, continuous carbon fiber bundles 1.5%, hexagonal boron nitride nanosheets 1%, tungsten carbide particles 0.4%, multilayer graphene 0.3%, sodium molybdate 0.25%, coupling agent 0.3%, lubricant 0.15%, oxidant 0.1%.

[0072] Electrolytic copper, aluminum bronze alloy, micron-grade nickel powder and chromium-molybdenum alloy are placed in a resistance melting furnace for melting at a temperature of 1200°C for 2 hours, and then the melt is poured into a sand mold and slowly cooled to room temperature to obtain a copper-based alloy ingot.

[0073] The ingot was broken into small pieces by a jaw crusher, and the small pieces were processed into particles by milling. The ball milling process was performed using carbon steel balls as the ball-to-material ratio of 3:1, the ball milling time was 4 hours, and the ball milling speed was 150 rpm. The continuous carbon fiber bundle was treated with chemical cleaning.

[0074] The pretreated electrolytic copper, aluminum bronze alloy, micron-sized nickel powder, chromium-molybdenum alloy, nano-silicon carbide particles, continuous carbon fiber bundles after chemical cleaning, hexagonal boron nitride nanosheets and tungsten carbide particles, as well as multilayer graphene, sodium molybdate, coupling agent, lubricant and antioxidant are added to a ball mill for ball milling. The ball milling speed is 200 r / min, the ball milling time is 4 hours, and then the ball-milled powder is naturally dried.

[0075] The mixed powder is loaded into a mold and subjected to cold pressing on a press machine at a pressure of 100 MPa.

[0076] The formed green body was placed in a sintering furnace and heated to 900°C at a constant rate of 8°C / min and kept at this temperature for 2 hours. The vacuum degree of the sintering furnace was 1×10 -2 Pa.

[0077] The sintered copper-based static disk material is machined, and then a metal ceramic coating is directly sprayed on the surface of the material using a spraying process.

[0078] Comparative Example 2 Material components: electrolytic copper 64%, aluminum bronze alloy 16%, nano nickel powder 6%, chromium-molybdenum alloy 7%, nano silicon carbide particles 2%, continuous carbon fiber bundles 1.5%, hexagonal boron nitride nanosheets 1%, tungsten carbide particles 1%, multilayer graphene 0.5%, sodium molybdate 0.2%, coupling agent 0.6%, nano molybdenum disulfide 0.1%, hindered phenol antioxidant 0.1%.

[0079] Electrolytic copper, aluminum bronze alloy, nano nickel powder and chromium-molybdenum alloy are placed in a vacuum induction melting furnace for vacuum induction melting at a melting temperature of 1350°C for 3.5 hours. During the vacuum induction melting process, electromagnetic stirring is used, and then the melt is poured into a water-cooled copper mold and quickly cooled to room temperature to obtain a copper-based alloy ingot; the copper-based alloy ingot is subjected to a single-pass hot rolling treatment at a hot rolling temperature of 950°C; the nano silicon carbide particles are immersed in a dopamine solution with a concentration of 1g / L and a pH value of 7, and the reaction is stirred at room temperature for 12 hours, and then the nano silicon carbide particles are taken out and rinsed with deionized water, and dried at 70°C for 3 hours; the continuous carbon fiber bundle is subjected to plasma treatment, and the treatment time The reaction time is 0.5 hours, the power is 300W, and then the impregnation treatment is carried out with a silane coupling agent, the treatment time is 1 hour, the temperature is 50°C, and the treated continuous carbon fiber bundles are dried at 90°C for 2 hours; the hexagonal boron nitride nanosheets are immersed in a sodium hydroxide solution with a concentration of 0.5 mol / L, stirred and reacted at 70°C for 1 hour, and then rinsed with deionized water to neutrality, dried at 90°C for 3 hours, and then modified with a silane coupling agent, the treatment time is 1 hour, and the temperature is 50°C; the tungsten carbide particles are ball-milled, the ball-milling medium is zirconium oxide balls, the ball-to-material ratio is 6:1, the ball-milling time is 10 hours, and the ball-milled tungsten carbide particles are dried at 70°C for 3 hours.

[0080] The pretreated electrolytic copper, aluminum bronze alloy, nano nickel powder, chromium-molybdenum alloy, nano silicon carbide particles, continuous carbon fiber bundles, hexagonal boron nitride nanosheets and tungsten carbide particles, as well as multilayer graphene, sodium molybdate, coupling agent, nano lubricant and antioxidant are added to a high energy ball mill for ball milling. The ball milling speed of the high energy ball mill is 250 r / min, and the ball milling time is 5 hours. During the ball milling process, acetone is added, and then the ball milled powder is vacuum dried at a drying temperature of 70°C for 3 hours.

[0081] The mixed powder is loaded into a mold, and then the mold is placed in a hot isostatic pressing device for hot isostatic pressing. The hot isostatic pressing temperature is 850° C., the pressure is 120 MPa, and the holding time is 1.5 hours.

[0082] The formed green body was placed in a vacuum sintering furnace and heated to 750°C at a rate of 6°C / min, kept at this temperature for 1 hour, and then heated to 1050°C at a rate of 2°C / min, kept at this temperature for 2.5 hours. The vacuum degree of the vacuum sintering furnace was 5×10 - 4 Pa.

[0083] The sintered copper-based static disk material was machined, and the surface was treated with aluminum oxide sandblasting at a pressure of 0.4 MPa with a particle size of 30 mesh. Then, the metal ceramic coating was sprayed on the surface of the material by high-speed flame spraying. The gas flow rate was controlled at 120 liters / minute, the oxygen flow rate was controlled at 300 liters / minute, and the powder feeding rate was 20 grams / minute. Then, the static disk material was placed in the vacuum chamber of the ion implantation equipment and evacuated to 5×10 -4 Pa, nitrogen ion implantation was performed, the energy of the implanted nitrogen ions was 60keV, and the dose was During the implantation process, the ion beam current density was controlled to be 6μA / cm².

[0084] The following is a comparison table of the performance parameters of the copper-based static disk materials of Examples 1-6 and Comparative Examples 1 and 2:

[0085] By comparison, in terms of hardness, the material hardness of the embodiment group is higher than that of the comparative group as a whole. The material hardness of embodiment six is ​​the highest, which is 946HV. The hardness of comparative example one is only 202HV, which is much lower than that of the embodiment. This is because it adopts resistance melting furnace smelting, the temperature is relatively low and the time is short, the alloy composition cannot be fully homogenized, and the treatment of the strengthening phase is relatively simple. For example, the continuous carbon fiber bundle is only chemically cleaned, resulting in poor dispersion of the strengthening phase in the matrix, and the strengthening effect cannot be effectively exerted. The hardness of comparative example two is 238HV. Although vacuum induction melting is adopted, the process parameters are not as optimized as those of the embodiment. For example, the pretreatment solution concentration of nano silicon carbide particles is low and the reaction time is short, which makes the strengthening effect of the strengthening phase poor.

[0086] In terms of strength, the strength of Example 6 reaches 946MPa, which is due to its higher content of nano-nickel powder and chromium-molybdenum alloy. These elements form solid solution strengthening and second phase strengthening in the alloy. At the same time, multiple hot rolling, appropriate annealing treatment, hot isostatic pressing and hot extrusion processes refine the grains and improve the organizational structure, thereby increasing the strength of the material. The strength of Example 4 is 898MPa, which is relatively low because its component ratio and process parameters are at a lower level in the embodiment group, but it is still higher than the control example. On the whole, with the increase of the content of strengthening elements in the composition and the optimization of the process, the strength gradually increases, indicating the importance of the synergistic effect of composition and process on strength improvement. The strength of comparative example 1 is only 628MPa. Due to its ordinary electrolytic copper and high proportion, the strength of the alloy matrix is ​​limited. In addition, there are deficiencies in the smelting and forming processes, such as low cold pressing pressure, which cannot densify the material and there are many defects inside, resulting in low strength. The strength of comparative example 2 is 785MPa. Although there are strengthening elements such as nano-nickel powder, the content and process parameters are not as good as those of the embodiment group. For example, the hot isostatic pressing temperature and pressure are low, and the holding time is short, which makes the material's organizational structure not dense enough and the strength is lower than that of the embodiment group.

[0087] In terms of friction coefficient, the friction coefficient of the embodiment group is between 0.31-0.36, which is relatively stable and relatively low. This is because the material contains friction performance regulators such as multilayer graphene and sodium molybdate, and the reinforcing phases such as nano silicon carbide particles and hexagonal boron nitride nanosheets also have a certain effect on friction performance. During the friction process, multilayer graphene and sodium molybdate form a lubricating film at the friction interface, reducing the direct contact between the materials and reducing the friction coefficient. The friction coefficient of embodiment three is as low as 0.31, which is due to the comprehensive optimization of its component ratio and process parameters, so that each friction performance regulator and reinforcing phase synergy effect is the best. The friction coefficient of comparative example one is as high as 0.42, mainly because it lacks an effective friction performance regulator synergy mechanism, the reinforcing phase is unevenly dispersed and poorly processed, and a stable lubrication structure cannot be formed during the friction process, resulting in large friction resistance on the surface of the material. The friction coefficient of comparative example two is 0.39. Although there are certain friction performance regulators, due to the insufficiency of components and processes, such as poor processing effect of nano silicon carbide particles, the friction coefficient is higher than that of the embodiment, indicating that its design and process implementation in terms of tribological performance are not as perfect as the embodiment.

[0088] In terms of wear rate, the wear rate of the embodiment is relatively low, between 0.044-0.056mm / 10 simulated landings. This is due to the combined effect of the high strength, high hardness and good tribological properties of the material. The uniform distribution of the reinforcing phase improves the wear resistance of the material, and the friction performance regulator reduces the friction coefficient and reduces wear. The wear rate of Example 3 is as low as 0.044mm / 10 simulated landings, and its comprehensive performance is the best, which can effectively resist wear during the friction process. The wear rate of Comparative Example 1 is as high as 0.107mm / 10 simulated landings. Because of its low strength, low hardness and high friction coefficient, the surface of the material is easily worn during the friction process of simulated landing, and it lacks effective wear-resistant structures and mechanisms. The wear rate of Comparative Example 2 is 0.083mm / 10 simulated landings. Although it is worse than Comparative Example 1, it is still far inferior to the embodiment in terms of wear resistance due to its defects in composition and process. This shows that the embodiment has significant advantages in improving wear resistance in material design and preparation process.

[0089] In terms of corrosion degree, the corrosion degree of the embodiment is relatively low, between 0.011-0.025mm / year. This is because the material contains hindered phenol antioxidants, phosphite antioxidants, chromium-molybdenum alloys and other components with certain corrosion resistance, and the dense microstructure also helps to prevent the invasion of corrosive media. The corrosion degree of Example 3 is as low as 0.011mm / year. The optimization of its composition and process makes the material have the best corrosion resistance. The corrosion degree of Comparative Example 1 is as high as 0.057mm / year. Due to its lack of effective antioxidant and corrosion-resistant system, ordinary electrolytic copper is easily corroded, and the internal structure of the material is loose, and the corrosive medium easily penetrates into the material, causing serious corrosion. The corrosion degree of Comparative Example 2 is 0.036mm / year. Although there are certain antioxidants, the insufficient content and process make its corrosion resistance not as good as that of the embodiment, which shows that the embodiment has more advantages in corrosion-resistant design and process, and can effectively improve the service life of the material in harsh environments.

[0090] It should be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, commodity or device. In the absence of further restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the process, method, commodity or device including the elements.

[0091] Each embodiment of the present invention is described in a progressive manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.

[0092] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present disclosure is limited to these examples. Based on the concept of the present disclosure, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of different aspects of one or more embodiments of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0093] While the disclosure has been described in conjunction with specific embodiments thereof, many alternatives, modifications and variations of these embodiments will be apparent to those skilled in the art in light of the foregoing description.

[0094] One or more embodiments of the present invention are intended to cover all such replacements, modifications and variations that fall within the scope of protection of the present invention. Therefore, any omissions, modifications, equivalent replacements, improvements, etc. made within the spirit and principles of one or more embodiments of the present invention should be included in the scope of protection of this disclosure.

Claims

1. A copper-based static disk material for aviation, characterized in that: The aviation copper-based static disk material includes, by mass percentage: 55%-65% high-purity electrolytic copper, 10%-15% aluminum bronze alloy, 4%-8% nano nickel powder, 2%-5% chromium-molybdenum alloy, 2%-6% nano silicon carbide particles, 1.5%-4% continuous carbon fiber bundles, 1%-3% hexagonal boron nitride nanosheets, 0.5%-2% tungsten carbide particles, 0.5%-2% multilayer graphene, 0.3%-1.5% sodium molybdate, 0.5-1.5% coupling agent, 0.2%-1% nano lubricant and 0.1%-0.8% antioxidant.

2. The aviation copper-based static disk material according to claim 1, characterized in that: The coupling agent comprises 0.3%-0.9% of a silane coupling agent and 0.2%-0.6% of a titanate coupling agent.

3. The aviation copper-based static disk material according to claim 1, characterized in that: The nano lubricant comprises 0.1%-0.5% of nano molybdenum disulfide and 0.1%-0.5% of nano zinc borate.

4. The aviation copper-based static disk material according to claim 1, characterized in that: The antioxidant comprises 0.05%-0.4% of hindered phenol antioxidant and 0.05%-0.4% of phosphite antioxidant.

5. A method for preparing an aviation copper-based static disk material according to any one of claims 1 to 4, characterized in that: The preparation method comprises: S1: Pretreatment of high-purity electrolytic copper, aluminum bronze alloy, nano nickel powder, chromium-molybdenum alloy, nano silicon carbide particles, continuous carbon fiber bundles, hexagonal boron nitride nanosheets and tungsten carbide particles; S2: adding the pretreated high-purity electrolytic copper, aluminum bronze alloy, nano nickel powder, chromium-molybdenum alloy, nano silicon carbide particles, continuous carbon fiber bundles, hexagonal boron nitride nanosheets and tungsten carbide particles, multilayer graphene, sodium molybdate, coupling agent, nano lubricant and antioxidant into a high energy ball mill for ball milling; S3: loading the mixed powder into a mold, and then placing the mold in a hot isostatic pressing device for hot isostatic pressing; S4: placing the formed green body into a vacuum sintering furnace and sintering it in a staged heating manner, and then performing hot extrusion treatment; S5: Mechanically process and surface treat the sintered copper-based static disk material.

6. The method for preparing the aviation copper-based static disk material according to claim 5, characterized in that: Step S1 specifically includes: S11: placing high-purity electrolytic copper, aluminum bronze alloy, nano nickel powder and chromium-molybdenum alloy in a vacuum induction melting furnace for vacuum induction melting, the melting temperature is 1300-1500° C., the melting time is 3-5 hours, during the vacuum induction melting process, the metal alloy is treated by a combination of electromagnetic stirring and ultrasonic treatment, and then the melted alloy is cooled, hot rolled, annealed and crushed in sequence; S12: soaking the nano-silicon carbide particles in a dopamine solution, wherein the concentration of the dopamine solution is 2-4 g / L and the pH value is 8-9, stirring and reacting at room temperature for 24-48 hours, then taking out the nano-silicon carbide particles and rinsing them with deionized water, and drying them at 80-100° C. for 4-6 hours; S13: treating the continuous carbon fiber bundle with plasma for 1-2 hours at a power of 500-1000 W, then impregnating the continuous carbon fiber bundle with a silane coupling agent for 2-4 hours at a temperature of 60-80° C., and drying the treated continuous carbon fiber bundle at 100-120° C. for 3-5 hours; S14: soaking the hexagonal boron nitride nanosheets in a sodium hydroxide solution with a concentration of 1-2 mol / L, stirring the solution at 80-100° C. for 2-4 hours, then washing with deionized water until neutral, drying at 100-120° C. for 4-6 hours, and then modifying the nanosheets with a silane coupling agent for 2-4 hours at a temperature of 60-80° C.; S15: ball milling the tungsten carbide particles, using zirconium oxide balls as the ball milling medium, a ball-to-material ratio of (8-12):1, and a ball milling time of 15-20 hours. The ball milled tungsten carbide particles are dried at 80-100° C. for 4-6 hours.

7. The method for preparing the aviation copper-based static disk material according to claim 5, characterized in that: In step S2, the ball milling speed of the high energy ball mill is 300-500r / min, and the ball milling time is 6-10 hours. During the ball milling process, a dispersant is added, and then the ball milled powder is vacuum dried at a drying temperature of 80-100°C for 4-6 hours.

8. The method for preparing the aviation copper-based static disk material according to claim 5, characterized in that: In step S3, the temperature of hot isostatic pressing is 800-1000°C, the pressure is 150-200 MPa, and the holding time is 2-4 hours.

9. The method for preparing the aviation copper-based static disk material according to claim 5, characterized in that: In step S4, the vacuum sintering furnace is first heated to 600-800°C at a rate of 5-10°C / min, kept at this temperature for 1-2 hours, and then heated to sintering temperature 1000-1200°C at a rate of 3-5°C / min, kept at this temperature for 3-4 hours. The vacuum degree of the vacuum sintering furnace is 1×10 -4 -1×10 -3 Pa, the temperature of hot extrusion treatment is 750-900℃, and the extrusion ratio is (15-25):

1.

10. The method for preparing the aviation copper-based static disk material according to claim 5, characterized in that: In step S5, the surface treatment method is: the surface is subjected to aluminum oxide sandblasting at a pressure of 0.3-0.6 MPa, the treatment particle size is 20-40 mesh, and then a wear-resistant coating is sprayed with a thickness of 0.05-0.2 mm, and then nitrogen ion implantation is performed, the energy of the injected nitrogen ions is 50-100 keV, and the dosage is .

Citation Information

Patent Citations

  • Graphite fiber reinforced copper-based composite material for pantograph slide plate

    CN110157999A

  • Copper-based composite friction material containing modified sepiolite as well as preparation method and application of copper-based composite friction material

    CN117448623A

  • Powder metallurgy friction material for high-speed train brake pad and preparation method of powder metallurgy friction material

    CN118371708A

  • Processing of coper bared sintered friction materials

    KR1019980040589A

Cited By

  • Laser additive remanufacturing process for repairing compressor accessories

    CN120619384A

  • Wear-resistant steel knife board for engineering machinery and preparation process of wear-resistant steel knife board

    CN122358178A